Discovery and investigation of high-capacity cathode materials for next generation Li-ion batteries - Hao, R (2017)
Lithium ion (Li-ion) batteries are the current state of the art for electrochemical energy storage and there is increasing demand for Li-ion batteries with a higher energy density. To achieve such a goal, cathode materials with higher capacity are required. Layered lithium rich (Li-rich) cathode materials are considered as a potential cathode candidate for future high capacity Li-ion batteries, mainly due to their large reversibly capacity of about 250 mAh g-1. However, the underlying chemistry of these materials remains unclear. The goal of this D.Phil. project is to investigate the underlying chemistry of these materials, especially the origin of the extra capacity; then to explore new Li-rich cathode materials with high capacities. The Resorcinol - Formaldehyde gel (R-F gel) method was selected from three different synthesis methods for preparing the layered Li-rich materials, as the material obtained by this method presented stable and enhanced electrochemical performance. By using a variety of characterization methodologies, a detailed study on the 1st cycle of Li1.2Ni0.13Co0.13Mn0.54O2, an archetypal example of layered Li-rich materials, were carried out and the extra capacity was attributed to a reversible oxygen redox process. A model of this oxygen redox process was also proposed, suggesting the balance between ionicity and covalency of metal-oxygen (M-O) bond is essential for activating this reversible oxygen redox. Additionally, a study of the binder effects on a layered Li-rich cathode was carried out. It was demonstrated that different binders used in electrodes would influence the electrochemical performance of the layered Li-rich cathode. A subsequent work was to synthesize and investigate Li1.2Mn0.4Ti0.4O2, a disordered rock-salt Li-rich material, which also exhibits enormous capacity and 1st cycle load curve similar to the layered Li-rich materials. A reversible oxygen redox process was demonstrated to be responsible for its extra capacity by using a variety of characterization methodologies. Moreover, the rock-salt structure was found remaining stable in the 1st cycle. The study of disordered rock-salt Li1.2Mn0.4Ti0.4O2 brings a new perspective to the study of oxygen redox in Li-rich cathode materials.